Penanganan Pengungsi Afghanistan Di Indonesia: Turut Bertanggung Jawabkah Perwakilan Diplomatik Afghanistan Di Indonesia? - Jones Nathanael, Joshua; Yeti Puspita, Natalia (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
Apart from being intended to establish friendly relations, diplomatic relations are also carried out to improve cooperative relations in various fields. The objectives of this study include: 1) to find out whether the diplomatic representatives of Afghanistan in Indonesia are also responsible for handling Afghan refugees in Indonesia based on the 1961 Vienna Convention, 2) to find out how Indonesia's role as a receiving country in efforts to handle refugees from Afghanistan in Indonesia is based on the Convention. Wina 1961. This legal research uses the normative juridical legal method. Secondary data obtained through literature study is used as the main data. The findings of this study indicate that Afghan diplomatic representatives have no responsibility towards refugees from Afghanistan because they have abandoned their citizenship when they left their country. As a receiving country based on the 1961 Vienna Convention, Indonesia has played a role in handling refugees from Afghanistan by issuing Presidential Regulation no. 125/2016 concerning the Handling of Refugees from Abroad which is used as a normative and coordinative basis for Ministries / Agencies and in handling refugees from abroad by involving the role of the Regional Government.